Are New Zealand's new primary health organisations fit for purpose?. Issue 7580 (7th December 2006) - Gauld, Robin; Mays, Nicholas
Abstract : Attempts to make New Zealand's health care more equitable have resulted in rapid change. But the reforms are largely untested and their effects difficult to predict